Legge di Drero - De Rossi, Maria Ilaria (Axon, 2017)
This legal text was situated on the eastern wall of Apollo Delphiniosʼ temple in Dreros, Crete. The inscription is very important: itʼs the oldest law we have from ancient Greece, and itʼs the first in which the word polis appears. The law imposes a limit to the iteration of the kosmos political office, the most important office in Dreros; moreover, the law specifies some punishments in case of violation. There also is an oath to show the importance of this law, and it involves the kosmos, the damioi and the ikati of the polis (we donʼt know the last two offices). The inscription is decently well- preserved, but the particular sequence ΘΙΟΣΟΛΟΙΟΝ causes some problems, because its meaning isnʼt clear.